Kilka uwag na temat rodzinnoprawnych aspektów prowadzenia przez szkołę dokumentacji przebiegu nauczania w formie dziennika elektronicznego - Ogrodnik-Kalita, Agnieszka (PRAWO i WIĘŹ, 2025)
The school duty and learning duty are connected with the necessity of conducting a documentary of educational progress by the school. The subject of the article is selected family and legal aspects of using this solution by the school. First of all, the author focuses on the protection of the child’s personal rights, paying special attention to independence and the right to privacy. Moreover, the analysis was submitted to the situation in which the access to e-register has parents of the adult child. Special attention was devoted to the access to the e-register of the parent whose parental authority was limited to specified duties and rights in relation to the child person. The author took into consideration the jurisdiction of the Common Courts in this case and presented postulated procedures.